Regarding further prospects in innovation of the rule-making legislative basis - I. L. Nevzorov (Law and Safety)
In Ukraine, the idea of systematization and unification of regulations, due to which positive law arises and is formed, has been discussed and defended for a long time. At the same time, to date, attempts in Ukraine to pass a law on rule-making have not been finalized. With the introduction of the draft Law on Legislative Activity in the Verkhovna Rada of Ukraine and subsequent voting on it by parliamentarians in the first reading, the issue of further prospects for innovation of the legislative basis of rule-making was raised again. An analysis of the constitutional provisions on rule-making in Ukraine has been presented. The European experience of constitutionalization of rule-making has been analyzed and the need to list the list of sources of law in the basic legal act of the state and to define the basic provisions on rule-making has been emphasized. It has been emphasized that the European experience of constitutionalization of rule-making / law-making indicates that the constitution as the basic law should answer the question of whether the state should have a law on normative acts and rule-making or need a broader approach reflected in law-making. In Ukraine, the fundamental position of legal science needs to be constitutionalized, that by-laws cannot contain primary norms of law, especially since the European experience indicates the need for such a step. By-laws must be adopted on the basis of and in compliance with the provisions of the law. Attention is drawn to the fact that the basic concepts and constructions of the draft Law of Ukraine “On Law-making”, such as law-making and principles of law-making, need significant refinement, as they are based on controversial conceptual approaches.